Philological study and nationalism values in Pangudarasa manuscript - Febrian, Andika Rizky; Ekowati, Venny Indria; Wulan, Sri Hertanti (Direktorat Riset dan Pengabdian kepada Masyarakat UNY, 2025)
The Pangudarasa script contains the importance of maintaining national identity to avoid arrogance. This research aims to describe the values of nationalism in the Pangudarasa manuscript. This research uses a descriptive method with primary data from the Pangudarasa manuscript collection of the National Library of the Republic of Indonesia with code number NB 1076.The research data consists of linguistic units in the text that contain values of nationalism. Data collection was conducted through heuristic and hermeneutic readings. The main instrument in the research is the human instrument. Data analysis is conducted using descriptive analysis. Data validation was carried out with validity and reliability. Based on the research results, the values of nationalism found in the Pangudarasa text include: a) maintaining the unity and integrity of the nation, b) loving and using domestic products, c) preserving the reputation of the nation and state, d) committing to defend the country from foreign threats, e) using the national language correctly and properly, f) prioritizing the interests of the nation and state above personal interests, and g) loving and preserving local culture. The values of nationalism in the Pangudarasa text can serve as an example as a foundation for living a life of nationhood and statehood.